Transformative Islamic Education With Environmental View Towards Green School In The Era Of Society 5.0 - Nursikin, Mukh; Maslikhah , Maslikhah; Tayeb, Azmil (INSANI: Jurnal Ilmu Agama dan Pendidikan, 2025)
This type of research is field research in the form of a case study. Data was obtained through observation, interviews and documentation and triangulation. Analysis is carried out by reviewing all the data, reducing the data, arranging the data in one unit (display data), and conclusion drawing/verification. The research results show that (1) there are two main strategies, namely by transforming environmental education and Islamic religious education as a whole. (2) Implementation of Islamic education with an environmental perspective towards a Green School is carried out through the first three activities: intracurricular, cocurricular, and extracurricular. (3) The supporting factors for implementing PAI with an environmental perspective are that the school community has the attitude that environmental education is important, the school community realizes that humans are part of the environment, the urge to save the environment, the existence of the adiwiyata program, and the adiwiyata school community. Inhibiting factors include the level of seriousness in maintaining the environment towards a Green School is different, there are not many environmentally friendly agents living towards a Green School, not all school residents are good towards their environment.